Final tax regression - Prawira, Muhamad Indrawan Yudha; Frans, Leo; Destiana, Rezki (Scientax: Jurnal Kajian Ilmiah Perpajakan Indonesia, 2024)
The urgency of this research lies in the pressing need to address regressiveness in Indonesia's taxation system, particularly concerning the Final Income Tax. As such, this study aims to examine the implications of Final Income Tax on taxpayers, especially high-income individuals, and propose potential reforms to ensure fairness and progressivity in the tax regime. To achieve this objective, the research employs a combination of quantitative analysis and theoretical frameworks. Income data from High-Wealth Individuals (HWIs) is analyzed to assess the regressiveness of the Effective Tax Rate (ETR), with a specific focus on income components subject to Final Income Tax. Additionally, the study reviews existing literature on tax reform and draws insights from international best practices to formulate recommendations for policy improvements. By combining empirical analysis with theoretical insights, this research contributes to a deeper understanding of the challenges within Indonesia's taxation system and offers actionable recommendations for policymakers and Directorate General of Taxes as Indonesian tax authorities.